2002
DOI: 10.1002/cncr.10251
|View full text |Cite
|
Sign up to set email alerts
|

Detection of cell free Epstein–Barr virus DNA in sera from patients with nasopharyngeal carcinoma

Abstract: BACKGROUNDThe detection of tumor‐derived DNA within the circulation of patients with malignant disease using polymerase chain reaction (PCR)‐based strategies has opened a new avenue for the diagnosis and monitoring of these patients. Because of the universal association of Epstein–Barr virus (EBV) with the nonsquamous type of nasopharyngeal carcinoma (NPC; World Health Organization types II and III), the detection of cell free EBV DNA in sera from patients with NPC may be a valuable tool for monitoring the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
38
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 12 publications
4
38
0
1
Order By: Relevance
“…The sensitivity of EBV DNA was found to be only 38% for rT1 and 50% for rT2 local recurrence after radiotherapy by the same group of investigators recently (14). Low sensitivity (28%) for locoregional NPC recurrence was also reported by Hsiao et al (15), and the increase of PCR cycle can increase the sensitivity to 89% but was also found to increase the false-positive rate to 37%. EBV DNA is, therefore, not a satisfactory marker for locoregional recurrence.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…The sensitivity of EBV DNA was found to be only 38% for rT1 and 50% for rT2 local recurrence after radiotherapy by the same group of investigators recently (14). Low sensitivity (28%) for locoregional NPC recurrence was also reported by Hsiao et al (15), and the increase of PCR cycle can increase the sensitivity to 89% but was also found to increase the false-positive rate to 37%. EBV DNA is, therefore, not a satisfactory marker for locoregional recurrence.…”
Section: Discussionsupporting
confidence: 61%
“…The sensitivity and specificity of EBV DNA are not duplicative in different laboratories by different investigators, and it was, however, found to have low sensitivity or high false-positive rates in recent reports (12,14,15). The sensitivity of EBV DNA was found to be 56% by Chan et al (12) and is much more inferior than EBV antibodies.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Only 50% of our patients had detectable EBV DNA levels at diagnosis, a result that is similar to those reported for EBNA-1 assays (21). Recently, Hsiao et al showed that an increase in the number of PCR cycles from 35 to 50 cycles during EBNA-1 testing resulted in improved detection sensitivity from 35% to 75% but at the expense of specificity (22). An increase in the number of PCR cycles during Pol-1 testing (from 40 to 50 cycles) may be useful in improving DNA detection rate in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…It is conceptually distinct from other peripheral blood markers in that it directly measures tumor-derived EBV genomic material rather than an antibody response to genomic or peptidic components of the EBV. Although initial studies based on qualitative measurement systems showed that plasma EBV DNA has a sensitivity of only 59 -75% for diagnosis of NPC (33)(34)(35), its sensitivity in quantitative assays was as high as 90% (36 ). Such a diagnostic sensitivity appears to be at least as good as that of IgA-VCA, although direct comparative studies of the two markers have yet to be reported.…”
mentioning
confidence: 99%